Regarding the update of research infrastructure problems and support for young scientists in the current conditions - S. O. Pogribny; S. V. Bezpalko; I. V. Kritsak; D. Ye. Denischuk (Bulletin of Kharkiv National University of Internal Affairs)
In an article based on the interdisciplinary method of scientific research, national and international experience, theoretical developments and legislative initiatives an attempt was made to update the normative and legal material and generalization of scientific developments in the field of research infrastructure, with an emphasis on modern educational and scientific processes. A significant drawback on this path was that initiators of drafting the draft law “About scientific and scientific and technical activity” on issues of research infrastructure and support for young scientists the scientific base of the investigated problem is not sufficiently taken into account, which is most often seen in reasoning, to the explanatory note to the Draft Law. It is suggested to borrow the displayed ones in the article the ideas of scientists, and also emphasizes implementation further scientific research, especially regarding the latest scientific publications of Ukraine and the world in the specified direction. The need for constant monitoring and analysis is emphasized positive foreign practices of building a smart educational and scientific policy, which is a stimulus for the prospects of the development of science and the national economy in general. As suggestions, author’s works are offered, ideas and recommendations implemented during the recent events of the Russian-Ukrainian war, which can be the ideological base for to improve the Draft Law we are working on. It should be noted that open science is – this is the future of the ХХІ century. The world is moving towards an open research infrastructure, which is a positive trend, after all everyone has an opportunity in free access get acquainted with the authors’ work. Today, providing open access to scientific resources is a priority. Research and scientific infrastructure under martial law equates to the critical infrastructure of the state.